Mapping of Western Siberian heat flow (southeast) - Isaev, V. I.; Krutenko , D.S.; Lobova, G.A.; Osipova , E.N.; Starostenko, V. I. (Geofizicheskiy Zhurnal, 2022)
This paper maps the heat flow density from the pre-Jurassic basement within a large territory of oil accumulation (circa 120 thousand sq. km) in the South-East of Western Siberia. Values of heat flow, calculated for 201 deep wells, comprise a dataset for developing the map with contour lines for every 2 mW/m2. These values were calculated by solving the inverse problem of Geothermy — one-dimensional initial-boundary value problem for equation of thermal conductivity in a solid with the moving upper boundary. The accepted mathematical statement is sufficiently accurate for modeling near horizontal bedded sedimentary section: existence of heat flow convectional component is taken into account via calculation of an effective heat flow value. The map shows different types of anomalous features of heat flow density distribution. Previously it was stated for Western Siberian Plate that values of deep heat flow within positive tectonic structures of sedimentary cover are 5—20 % higher than within negative tectonic structures. As it is, combined analysis of deep heat flow density distribution and location of tectonic structures (Kaimysov arch, Parabelmegaarch, especially Alexandrov arch and Pudino mega swell) shows tendency among positive tectonic structures for increasing deep heat flow value. However, it is not always so. For example, there is the utterly different correlation for the Srednevasyugan mega swell. This structure is characterized with lower heat flow. The location of the Nizhnevartovsk arch is almost untraceable in the deep heat flow density distribution. Concerning oil-and-gas potential ... (?) A large positive anomaly has formed in the zone around the Traigorodsko-Kondakov field in the north. Two positive anomalies are in the central part of the map: around the Snezhnoe field and close by the Lomovoe, the Ozernoe and the Katylgin fields. Such fields as the Rybalnoe, the Pindzhin and the Mirnoe surround a positive anomaly in the southeastern part of the map. This paper contains a catalogue of discrete values (by wells) and a map of heat flow, which may be used as a «framework» in basin modeling. Upcoming research concerning origin of heat flow density anomalies — graded assessment of possible influence of tectonics, material composition and oil-and-gas potential of basement rocks has theoretical and practical significance.